Liver CEBPβ Modulates the Kynurenine Metabolism and Mediates the Motility for Hypoxia-Induced Central Fatigue in Mice - Yang, Fan; Zhou, Li; Song, Jun; WangJinMei, A; Yang, Yuan; Tang, Zhong-wei; Huang, Qing-Yuan (Frontiers in Physiology, 2019)
Central fatigue is defined as a failure of the central nervous system to adequately drive the muscle, manifesting limited development and maintenance of locomotor activity. A plateau in hypoxia leads to central fatigue, followed by maximal motility recession; however, the underlying mechanism is still unclear. The present study describes a mechanism by which liver CEBPβ (CCAAT/enhancer-binding protein beta) induced by hypoxic environment alters the kynurenine (KYN) metabolism and causes the suppression of motility function recession. The activation of CEBPβ under hypoxia increases the liver expression of tryptophan dioxygenase, thereby enhancing the conversion of tryptophan into KYN; the KYN metabolite can traverse the blood-brain barrier and result in the suppression of motility function. However, the knockdown of CEBPβ by injecting pAAV-shRNA-CEBPβ via the hepatic portal vein reduces the KYN production and improves the motility function. KYN is a neurochemical that which restricts the exercise capacity after injection in the basal ganglia in mice. Reducing the plasma KYN protects the brain from hypoxia-induced changes associated with fatigue, and the knockdown liver of CEBPβ in mice renders resistance to fatigue post-acute hypoxia or tryptophan treatment. This study reveals resistance to central fatigue as a strategy for acclimatization to hypoxia mediated by transcription factor CEBPβ in the liver.